A multi-analyte responsive chemosensor vanilinyl Schiff base: fluorogenic sensing of Zn(ii), Cd(ii) and I−. (18th September 2018) - Purkait, Rakesh; Dey, Sunanda; Sinhaa, Chittaranjan
Abstract : A single fluorescence probe recognizes multiple ions and grabs the great attention of scientists. Abstract : 6, 6′-((1E, 1′E)-((2E, 2′E)-((2-hydroxy-5-methyl-1, 3-phenylene)bis(methanylylidene))bis(hydrazine-2, 1-diylidene))bis(methanylylidene))bis(3-methoxyphenol). (H3 L ) is a multi-responsive vanilinyl- p -cresol diformyl Schiff base fluorescent chemosensor for Zn 2+ ( λ em, 545 nm), Cd 2+ ( λ em, 560 nm) (both in 9 : 1 (v/v) DMSO–water), and I − ( λ em, 630 nm in THF). The probe (H3 L ) is spectroscopically characterised and the chemosensing mechanism is demonstrated through 1 H NMR, ESI-MS, absorption and luminescence spectral data. The most promising advantage of the probe (H3 L ) is its application in the one-pot detection of Zn 2+ and Cd 2+ using excitation at the same wavelength ( λ ex, 482 nm) while highly intense emission appears at two different wavelengths. A detection kit is designed for drinking water analysis and has been checked to measure the quality of potable water in the locality. The sensor is also applied to construct an INHIBIT logic gate. Density Functional Theory (DFT) calculations are used to optimize the structure and the electronic properties are correlated with the experimental results.